THE NOTION OF TRANSLATION TECHNIQUES IN AUDIOVISUAL TRANSLATION - Akhmedova , Malikakhon ("Science Shine" International scientific journal, 2024)
Annotation: Although we are surviving in the era of technology, interpreters are still facing considerable amount of unsolved questions, challenges and interpretational issues belong to audiovisual translation. Additionally, grammar, punctual and cultural mistakes in subtitling and, dismissing or omitting the main information, to translate the source material in the wrong style in dubbing process are very common in translation. All of the above mentioned problematic conditions in interpretation will be discussed in this article.